2011
DOI: 10.1182/blood-2011-07-364661
|View full text |Cite
|
Sign up to set email alerts
|

Second induction with high-dose cytarabine and mitoxantrone: different impact on pediatric AML patients with t(8;21) and with inv(16)

Abstract: Patients with core binding factor acute myeloid leukemia (CBF-AML) benefit from more intensive chemotherapy, but whether both the t(8;21) and inv(16)/t (16;16) subtypes requires intensification remained to be determined. In the 2 successive studies (AML-BFM-1998 and AML-BFM-2004), 220 CBF-AML patients were treated using the same chemotherapy backbone, whereby reinduction with high-dose cytarabine and mitoxantrone (HAM) was scheduled for these cohorts only in study AML-BFM-1998 but not in AML-BFM-2004 against t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 30 publications
3
56
2
Order By: Relevance
“…Notably, AML-BFM 2004 was designed without HAM treatment in all SR patients, including those with t(8;21), unlike AML-BFM 98. We have shown 30 that second induction with HAM is beneficial for these patients. Nevertheless, we consider now that the more favorable activity of L-DNR over idarubicin in first induction could compensate at least partly for the lack of HAM.…”
Section: Discussionmentioning
confidence: 80%
“…Notably, AML-BFM 2004 was designed without HAM treatment in all SR patients, including those with t(8;21), unlike AML-BFM 98. We have shown 30 that second induction with HAM is beneficial for these patients. Nevertheless, we consider now that the more favorable activity of L-DNR over idarubicin in first induction could compensate at least partly for the lack of HAM.…”
Section: Discussionmentioning
confidence: 80%
“…31 The outcome of our SR patients was inferior to that reported by other groups. 3,[6][7][8]10,32 There is no obvious explanation for this result. Considering compliance with dose intensity as a possible reason for the outcome of our SR patients being worse than expected, the median treatment duration for SR patients was 170 days (range 135-210 days); the estimated median duration of treatment of SR patients was 140 days.…”
Section: Discussionmentioning
confidence: 90%
“…This delay could have partly contributed to the unsatisfactory outcome of SR children. The new AIEOP study will address the question of whether the use of flow-cytometry-based minimal residual disease detection, which is certainly much more sensitive than morphologic evaluation for monitoring early leukemia clearance 7 and/or early/repeated courses of mitoxantrone, 32 can improve the EFS of SR children. The worse outcome observed in patients with monosomal karyotype has been reported in adult patients, 33 but it is a relatively novel observation for childhood AML, since only the negative impact of monosomy 7 has been previously described.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the AML-BFM 98 and 2004 trials in patients with t(8;21) AML demonstrated a significant favorable impact of HiDAC plus mitoxantrone in second induction. 87 Additional agents. Other drugs that have been used during induction include aclarubicin, amsacrine (adults), mitoxantrone (children and adults), and 2-chlorodeoxyadenosine (children).…”
Section: Recommendationmentioning
confidence: 99%